Influence of rotational speed on mechanical features of thermally drilled holes in dual-phase steel. (April 2019) - Kumar, R; Hynes, N Rajesh Jesudoss
Thermal drilling is a novel chipless sheet metal drilling process that uses a rotating thermal drill tool to pierce and form a bushing shape hole. In this work, thermal drilling process is successfully employed to drill the DP 600 grade–type galvanized steel with a thickness of 2 mm. The influence of different spindle rotational speeds such as 1600, 2000 and 2400 r/min on the formation of bushing height, surface roughness, microhardness and microstructure of the thermal-drilled holes are investigated in detail. Process parameters such as feed rate, thermal drill angle and workpiece thickness were held constant in order to explore the influence of rotational speed on the quality characteristics of the thermal drilling process. It has been found that the bushing height was improved with increasing of rotational speed, but the petal formation at the outer edge of the bush is decreased. Surface roughness tests indicate that the better surface quality drilled hole could be obtained at the highest rotational speed of 2400 r/min. The microstructural investigation confirmed that a new result of Lüders band marks was formed inside the thermal-drilled holes because high thermal stress and yielding of galvanized steel material.